Estruturas de PLL (Phase-Locked Loop) monofásica e trifásica com alta rejeição a sub e inter-harmônicas - Araújo, Renato Guerreiro (2015)
In applications related to power converters, such as inverters, rectifiers and the use of active filters, the synchronization method represent a very important element in the performance of the control strategy of this equipment. The estimated values of the synchronism angle, frequency and amplitude determined by the synchronization algorithms present, facing strongly distorted signals with the presence of sub and interharmonics, high errors. This study presents two algorithms: one applied on single-phase electrical systems and one applied on three-phase electrical systems, with high immunity to interharmonics and subharmonics. First are presented the main synchronization systems that are used in the electrical power systems. In addition, will be presented the main causes and consequences of the presence of subharmonics and interharmnics in the system, as well as the mathematical modeling of the two algorithms with high rejection to these disturbances. Will be presented the simulation and the experimental results of the proposed algorithms and the comparison between these synchronization methods with particular methods present in the literature. As a result of the study, it can be seen that the proposed structures present a higher response time, but the error of the estimated signal with respect the fundamental component of the input signal is lower when compared to structures such as EPLL and structures based on SOGI. It was observed that the proposed synchronization methods are enabled to estimate the synchronism angle, the frequency and the fundamental component of the input signal adequately and can be used in control strategies of power converters.